Outcomes, indications and predictive factors for complications in postmastectomy prepectoral reconstructions with polyurethane foam-coated implants - Andrea Lisa; Francesca Riccardi; Mario Alessandri-Bonetti; Luca Mazzocconi; Manuela Bottoni; Benedetta Barbieri; Alessandra Gottardi; Marco Palmesano; Valerio Cervelli; Vincenzo Bagnardi; Eleonora Pagan; Paolo Veronesi; et al. (Breast)
Background: Implant-based reconstruction (IBR) is the most common reconstructive strategy following mastectomy. Advancements in surgical techniques and materials have led to improvement in perfusion and thickness of mastectomy skin flaps and they have renewed interest in prepectoral breast reconstruction (PBR).The aim of this study was to analyze the surgical outcomes of skin or nipple-sparing mastectomies with direct-to-implant (DTI) reconstructions with prepectoral polyurethane foam–coated implants. Methods: A retrospective study was conducted on consecutive patients undergoing postmastectomy IBR-DTI with prepectoral polyurethane foam-coated implants between 2020 and 2022. Inclusion criteria were a preoperative pinch test >0.8 cm and well-perfused mastectomy flaps. Preoperative radiation therapy was not an exclusion criterium. Complications were classified as “major” if they required urgent re-intervention, and as “minor” if they required only outpatient management. Results: A total of 250 patients and 317 breast reconstructions were included. The mean (±SD) age was 50.5 ± 10.9 years with a mean BMI of 23.8 ± 4.0. The mean follow-up was 12.2 ± 1.2 months. The overall rate of major complications was 6.3 %, being infection the most common major complication (2.5 %), followed by mastectomy flap necrosis (1.6 %), bleeding (1.6 %), and wound dehiscence (0.6 %). The overall minor complications rate was 27.8 %. Across minor complications, rippling was recorded as the most common (14.5 %), followed by capsular contracture (7.6 %), seroma formation (2.5 %), skin necrosis (2.2 %), hematoma (0.6 %) and wound dehiscence (0.3 %). Conclusion: In our cohort, DTI-PBR with PU implants had a 6.3 % risk of major complications requiring urgent re-intervention. Hypothyroidism, diabetes, and overweight have been identified as risk factors associated with higher risk of complications.